Assessment of Neuroprotective Properties of Melissa officinalis in Combination With Human Umbilical Cord Blood Stem Cells After Spinal Cord Injury. (October 2016) - Hosseini, Seyed Ruhollah; Kaka, Gholamreza; Joghataei, Mohammad Taghi; Hooshmandi, Mehdi; Sadraie, Seyed Homayoon; Yaghoobi, Kayvan; Mohammadi, Alireza
Introduction: The pathophysiology of spinal cord injury (SCI) has a classically bad prognosis. It has been demonstrated that human umbilical cord blood stem cells (hUCBSCs) and Melissa officinalis (MO) are useful for the prevention of neurological disease. Methods: Thirty-six adult male rats were randomly divided into intact, sham, control (SCI), MO, hUCBSC, and MO-hUCBSC groups. Intraperitoneal injection of MO (150 mg/kg) was commenced 24 hr post-SCI and continued once a day for 14 days. Intraspinal grafting of hUCBSCs was commenced immediately in the next day. The motor and sensory functions of all animals were evaluated once a week after the commencement of SCI. Electromyography (EMG) was performed in the last day in order to measure the recruitment index. Immunohistochemistry, reverse transcription-polymerase chain reaction, and transmission electron microscopy evaluations were performed to determine the level of astrogliosis and myelination. Results: The results revealed that motor function (MO-hUCBSC: 15 ± 0.3, SCI: 8.2 ± 0.37, p < .001), sensory function (MO-hUCBSC: 3.57 ± 0.19, SCI: 6.38 ± 0.23, p < .001), and EMG recruitment index (MO-hUCBSC: 3.71 ± 0.18, SCI: 1.6 ± 0.1, p < .001) were significantly improved in the MO-hUCBSC group compared with SCI group. Mean cavity area (MO-hUCBSC: 0.03 ± 0.03, SCI: 0.07 ± 0.004, p < .001) was reduced and loss of lower motor neurons (MO-hUCBSC: 7.6 ± 0.43, SCI: 3 ± 0.12, p < .001) and astrogliosis density (MO-hUCBSC: 3.1 ± 0.15, SCI: 6.25 ± 1.42, p < 0.001) in the ventral horn of spinal cord were prevented in MO-hUCBSC group compared with SCI group. Conclusion: The results revealed that the combination of MO and hUCBSCs in comparison with the control group has neuroprotective effects in SCI.